PERANCANGAN MODEL REPRESENTASI PENGETAHUAN BERBASIS ONTOLOGI PADA APLIKASI SIPELANTIK: STUDI KASUS PUSINTEK KEMENTERIAN KEUANGAN - Andrianto Susilo; Putu Wuri Handayani; Iik Wilarso (Faculty of Computer Science Universitas Indonesia, 2015)
In supporting the implementation of ICT service management, Pusat Sistem Informasi dan Teknologi Keuangan (Pusintek) already have the Sistem Pengelolaan Layanan Teknologi Informasi dan Komunikasi (Sipelantik) application. This application is the automation of ICT service management business process, especially in the area of Service Support. In practice, the knowledge generated from this business process has broad enough coverage. However, these knowledges are not easily retrieved. Thus, a model that can describe and connect the knowledge is demanded. This study proposes a model of ontology-based ICT services knowledge representation using the existing knowledge on the Sipelantik application. The Ontology models are developed by software Protege in the form of Web Ontology Language (OWL). Simple Protocol And RDF Query Language (SPARQL) and Description Logic (DL) Query are used to obtain the information and knowledge from OWL models and to ensure that the relationships between concepts are properly defined. Reasoner Pellet plugin is used to ensure the consistency of the built ontology models. This research results in six classes of knowledge (knowledge base, role, service request, incident handling, component configuration, and service catalog) including the subclasses and an ontology model as knowledge of ICT services that can be shared and reused.